From the Editor - Judith A. Holton (Grounded Theory Review: An International Journal, 2011)
In 2009, we issued a special call for papers, Along the GT Learning Curve, to focus on the novice experience in learning and doing Classic Grounded Theory (CGT). We especially welcomed papers that demonstrate the challenges, rewards and lessons learned and that offered advice to others undertaking their first CGT study. It has taken some time to bring this issue to publication; to select the papers and to work through various iterations of review and revision. We are very pleased to finally present this issue with six papers from a wide range of professional fields including business, psychology, education, social work and medical sociology. The range of disciplines alone speaks to the reach of CGT as a research methodology.